A little less aggregation a little more replication: Viral manipulation of stress granules. (16th June 2022) - Brownsword, Matthew J.; Locker, Nicolas
Abstract: Recent exciting studies have uncovered how membrane‐less organelles, also known as biocondensates, are providing cells with rapid response pathways, allowing them to re‐organize their cellular contents and adapt to stressful conditions. Their assembly is driven by the phase separation of their RNAs and intrinsically disordered protein components into condensed foci. Among these, stress granules (SGs) are dynamic cytoplasmic biocondensates that form in response to many stresses, including activation of the integrated stress response or viral infections. SGs sit at the crossroads between antiviral signaling and translation because they concentrate signaling proteins and components of the innate immune response, in addition to translation machinery and stalled mRNAs. Consequently, they have been proposed to contribute to antiviral activities, and therefore are targeted by viral countermeasures. Equally, SGs components can be commandeered by viruses for their own efficient replication. Phase separation processes are an important component of the viral life cycle, for example, driving the assembly of replication factories or inclusion bodies. Therefore, in this review, we will outline the recent understanding of this complex interplay and tug of war between viruses, SGs, and their components. This article is categorized under: RNA in Disease and Development > RNA in Disease Translation > Regulation RNA Interactions with Proteins and Other Molecules > RNA‐Protein Complexes Abstract : Viruses depend entirely on host machinery and therefore aim to conquer the host and defeat its defenses to co‐opt its resources for its own replication. Improved understanding of how viruses counteract host immune responses such as stress granule assembly, detailed here, will inform future antiviral therapeutic strategies.